Maya Angelou’s Poems “Still I Rise” and “Woman Work”: Voices of Defiance on Female Violence and Resistance - Suhadi, Agung (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article explores the complex portrayal of female violence and resistance in Maya Angelou’s poetry. By examining key poems, this study uncover how Angelou addresses the dynamics of power, suffering, and resilience, highlighting the poet’s unique voice in confronting and transcending the violence experienced by women. Her poems